High-strength polyethylene composition and preparation method thereof

By using a variety of polyethylene resins and reinforced fibers in the polyethylene material, the problems of insufficient strength and high shrinkage rate of existing polyethylene materials are solved, and the effects of high strength, low shrinkage rate and multiple recycling are achieved, meeting the production needs of large pallets, plates and other products.

CN119899440APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311391176.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing polyethylene materials are insufficient in large pallets, plates and other products, with high shrinkage and poor durability, making it difficult to meet the transportation industry's demand for dimensional stability and multiple recycling.

Method used

High-strength, high-strength, high-strength, low-strength polyethylene resin, linear low-density polyethylene resin, peroxide crosslinking agent, activated calcium carbonate, reinforced fibers and antioxidants are used to prepare high-strength, high-strength, and low shrinkage polyethylene compositions through scientific and reasonable formulation and processing technology.

Benefits of technology

It has achieved high strength, low shrinkage, good dimensional stability and multiple recycling capabilities of polyethylene products, meeting the production needs of large pallets, plates and other products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004512432570000111
    Figure BDA0004512432570000111
  • Figure BDA0004512432570000121
    Figure BDA0004512432570000121
  • Figure BDA0004512432570000122
    Figure BDA0004512432570000122
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a high-strength polyethylene composition and a preparation method thereof. The high-strength polyethylene composition is composed of high-density polyethylene, medium-density polyethylene, linear low-density polyethylene, activated calcium carbonate, reinforced fibers, peroxide and an antioxidant. The impact strength of a simply supported beam notch is 50-70 kJ / m < 2 >, the bending elastic modulus is 1300-2000 MPa, the shrinkage rate is smaller than 0.7%, the creep elongation rate is smaller than 5% after a test is conducted for 800 h under the tensile force of 120 N, and the environmental stress cracking resistance time is longer than 500 h. The polyethylene material can be used for preparing large polyethylene trays or plate products through injection molding or compression molding, and the produced products are high in strength, good in impact resistance, low in shrinkage rate and good in stress cracking resistance, can be recycled for multiple times and can be used for a long time under the conditions of stress bending, deformation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-strength polyethylene composition and a preparation method thereof. Background Art

[0002] High-density polyethylene (HDPE) has the advantages of high strength, good durability and excellent chemical stability. It is the most widely used resin raw material for producing plastic pallets, sheets, barrels and other plastic products that have high requirements for mechanical strength, durability and aging resistance.

[0003] With the development of the transportation industry, the size of pallet products needs to be larger and larger in order to be used for the transportation of larger products. There is also a greater demand for the size of products such as plates. Therefore, the requirements for the strength and toughness of the polyethylene raw materials used are getting higher and higher. At the same time, as the size of plastic products becomes larger and larger, the requirements for the shrinkage rate of product molding are also getting higher and higher. If the shrinkage rate of plastic raw materials is large, the shrinkage of pallets, plates and other products processed by injection molding and compression molding will be greater after demolding, and the shrinkage of products after demolding is also greatly affected by ambient temperature, product demolding temperature, etc., resulting in differences in product size and inability to deliver for use. In addition, the number of times pallets, plates and other products are recycled is one of their important quality indicators. The more times they are recycled, the lower the transportation investment cost will be. Therefore, the strength and durability requirements for the raw materials used to produce pallets, plates and other products are also getting higher and higher. Usually, pallets, plates and other products are subjected to pressure, tension, bending, impact and other forces during use. When subjected to force for a long time, the material needs to have a high creep resistance.

[0004] Patent CN113930039A discloses a bamboo-plastic composite board material for container bottom plates, whose raw material components include modified bamboo pulp fiber, HDPE, LLDPE, sarin resin, maleic anhydride grafted polypropylene, polyethylene wax, and thermotropic liquid crystal polymer. The prepared bamboo-plastic composite board material has excellent mechanical properties and low water absorption, but its raw material preparation process is complicated and its strength still needs to be improved. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a high-strength polyethylene composition, which has high strength, high toughness, low shrinkage and creep resistance. The plastic products produced by the high-strength polyethylene composition have high strength, low shrinkage, good dimensional stability and durability, and can be recycled many times, meeting the production of large injection molding and compression molding products such as pallets and plates;

[0006] Another object of the present invention is to provide a method for preparing a high-strength polyethylene composition, which is scientific, reasonable, simple and easy to implement.

[0007] The technical solution adopted by the present invention is as follows:

[0008] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0009] High-density polyethylene resin: 33.7-68.9%

[0010] Medium density polyethylene resin: 10-20%

[0011] Linear low density polyethylene resin: 10-20%

[0012] Peroxide crosslinker: 1-6%

[0013] Activated calcium carbonate: 5-10%

[0014] Reinforcement fiber: 5-10%

[0015] Antioxidant: 0.1-0.3%.

[0016] The high-density polyethylene resin has 1-hexene as a comonomer, and the content of the comonomer is 0.8-1.0%; the melt mass flow rate of the high-density polyethylene resin is 0.2-1g / 10min at a temperature of 190°C and a weight of 5kg; the density is 0.948-0.953g / cm 3 ; Weight average molecular weight is (20-35)×10 4 , preferably (25-30)×10 4 ; The molecular weight distribution width is 25-35, preferably 28-33.

[0017] The medium density polyethylene resin uses 1-hexene as a comonomer, and the content of the comonomer is 1-1.2%; the melt mass flow rate of the medium density polyethylene resin is 0.3-1g / 10min at a temperature of 190°C and a weight of 2.16kg; the melt mass flow rate is 15-25g / 10min at a temperature of 190°C and a weight of 21.6kg, the melt flow ratio is 30-60, and the density is 0.935-0.940g / cm 3 The number of long branch chains with a length greater than 6 carbon atoms in the molecule tested by nuclear magnetic resonance is more than 5 / 1000C.

[0018] The melt mass flow rate of the linear low-density polyethylene resin is 1.5-2.5 g / 10 min at a temperature of 190°C and a weight of 2.16 kg, and the density is 0.917-0.923 g / cm 3 .

[0019] The peroxide crosslinking agent is one or more of alkyl peroxide, aryl peroxide, acyl peroxide or ketone peroxide, and the amount used is 1-6%, preferably 3-5%.

[0020] The activation degree of the activated calcium carbonate is above 98%, and the dosage is 5-10%, preferably 7-9%. The preparation method is as follows: drying the calcium carbonate at 105°C for more than 3 hours, placing it in a mixer and heating it to above 80°C, adding an activator twice, the activator can be selected from but not limited to aluminate coupling agent, titanate coupling agent, aluminum-titanium composite coupling agent, etc., and stirring for more than 60 minutes. The particle size of the calcium carbonate is 800-2000 mesh.

[0021] The aspect ratio of the reinforcing fiber is greater than 100:1, preferably greater than 500:1, and the reinforcing fiber is one of carbon fiber, glass fiber or wood cellulose.

[0022] The antioxidant is obtained by mixing antioxidant 1010 and antioxidant 168, and the mixing ratio is 1:(0.5-2), preferably 1:1.

[0023] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0024] (1) weighing each component of the composition in proportion, stirring and mixing the linear low-density polyethylene resin and the reinforcing fiber, and melt-extruding and granulating them using a low-shear wide-screw single-screw extruder to obtain a mixture;

[0025] (2) The mixture obtained in step (1) is mixed with a high-density polyethylene resin, a medium-density polyethylene resin, a peroxide crosslinking agent, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 4-6 minutes, stirred evenly, melt-extruded and granulated in a twin-screw extruder to obtain a high-strength polyethylene composition.

[0026] In the step (1), the extrusion temperature of the single screw is 130-190°C; and in the step (2), the extrusion temperature of the twin screw is 150-230°C.

[0027] During the preparation process, linear low-density polyethylene and reinforcing fibers are first melt-mixed and extruded, so that the aspect ratio of the reinforcing fibers can be better maintained; the use of medium-density polyethylene containing more long-chain branches further improves the mixing effect of the components of the composition, and at the same time promotes the ability to resist stress damage; through the combined application of the components, a high-strength, high-impact, low-shrinkage and creep-resistant polyethylene composition is finally obtained.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention develops a high-strength polyethylene composition formula by screening the components of the composition formula, analyzing and characterizing the basic physical properties, and examining the processing and use performance, and obtains the high-strength polyethylene composition, whose density is 0.95-1.05g / cm 3, simply supported beam notched impact strength is 50-70kJ / m 2 , bending elastic modulus is 1300-1800MPa, shrinkage is less than 0.7%, creep elongation is less than 5% after 800h test under 120N tensile force, and environmental stress cracking resistance time (50℃) is greater than 500h. It can be used for injection molding or compression molding of large polyethylene pallets or sheet products. The products produced have the advantages of high strength, good impact resistance, low shrinkage, etc. At the same time, they also have good stress cracking resistance, and can be used for multiple cycles and long-term use of products under stress bending, deformation, etc.;

[0030] (2) The preparation method of the present invention is scientific, reasonable, simple and easy to implement. DETAILED DESCRIPTION

[0031] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples are conventional commercially available products.

[0033] in:

[0034] The melt mass flow rate of high-density polyethylene resin 1 (weight 5kg, temperature 190°C) is 0.38g / 10min; the density is 0.951g / cm 3 ; 1-hexene is used as the comonomer, and the content of the comonomer is 0.9%; the weight average molecular weight is 31×10 4 ; The molecular weight distribution width is 29.

[0035] The melt mass flow rate of high-density polyethylene resin 2 (weight 5kg, temperature 190°C) is 0.35g / 10min; the density is 0.949g / cm 3 ; 1-hexene is used as the comonomer, and the content of the comonomer is 0.97%; the weight average molecular weight is 33×10 4 ; The molecular weight distribution width is 25.

[0036] High-density polyethylene resin 3 has 1-butene as a comonomer, and its melt mass flow rate (weight 5kg, temperature 190°C) is 0.56g / 10min and density is 0.946g / cm 3 .

[0037] The melt mass flow rate (weight 2.16 kg, temperature 190°C) of medium density polyethylene resin 1 is 0.35 g / 10 min, the melt mass flow rate (weight 21.6 kg, temperature 190°C) is 22.6 g / 10 min; the density is 0.937 g / cm 3; 1-hexene is used as the comonomer, and the comonomer content is 1.1%; the melt flow ratio is 43, and the number of long branch chains with a length greater than 6 carbon atoms in the molecule tested by nuclear magnetic resonance is 6 / 1000C.

[0038] The melt mass flow rate (weight 2.16 kg, temperature 190°C) of the medium density polyethylene resin 2 is 0.4 g / 10 min, the melt mass flow rate (weight 21.6 kg, temperature 190°C) is 21 g / 10 min; the density is 0.937 g / cm 3 ; 1-hexene is used as the comonomer, and the comonomer content is 1.2%; the melt flow ratio is 52, and the number of long branch chains with a length greater than 6 carbon atoms in the molecule tested by nuclear magnetic resonance is 6.3 / 1000C.

[0039] The melt mass flow rate (weight 2.16 kg, temperature 190°C) of the medium density polyethylene resin 3 is 0.37 g / 10 min, and the melt mass flow rate (weight 21.6 kg, temperature 190°C) is 23.5 g / 10 min. The density is 0.936 g / cm 3 , with 1-hexene as the comonomer, the comonomer content is 0.7%, and the number of long branch chains with a length greater than 6 carbon atoms in the molecule tested by nuclear magnetic resonance is 2.8 / 1000C.

[0040] The melt mass flow rate of linear low-density polyethylene resin 1 (weight 2.16 kg, temperature 190°C) is 1.9 g / 10 min; the density is 0.921 g / cm 3 .

[0041] The melt mass flow rate of linear low-density polyethylene resin 2 (weight 2.16 kg, temperature 190°C) is 2.5 g / 10 min; the density is 0.923 g / cm 3 .

[0042] The peroxide crosslinking agent is di-tert-butyl peroxide.

[0043] The activation degree of activated calcium carbonate is 99%. The preparation method is as follows: drying calcium carbonate at 105°C for 3.1 hours, placing it in a mixer and heating it to 80°C, adding an aluminate coupling agent twice in an amount of 2%, stirring for 60 minutes, and obtaining activated calcium carbonate. The particle size of the calcium carbonate is 1250 mesh.

[0044] The aspect ratio of wood cellulose is 1000:1, the lignin content is 30%, and the cellulose content is 50%.

[0045] The aspect ratio of the glass fiber is 500:1 and the diameter is 30um.

[0046] The antioxidant is obtained by mixing antioxidant 1010 and antioxidant 168 in a mixing ratio of 1:1.

[0047] Example 1

[0048] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0049] High density polyethylene resin 1: 52.8%

[0050] Medium density polyethylene resin 1: 15%

[0051] Linear low density polyethylene resin 1: 15%

[0052] Di-tert-butyl peroxide: 3%

[0053] Activated calcium carbonate: 9%

[0054] Lignocellulose: 5%

[0055] Antioxidant: 0.2%.

[0056] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0057] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 1 and the wood cellulose, and melt-extruding and granulating them using a low-shear wide-screw single-screw extruder, wherein the temperatures of each section of the single-screw extruder are 130° C. for the first section, 150° C. for the second section, 160° C. for the third section, 180° C. for the fourth section, and 190° C. for the fifth section, to obtain a mixture;

[0058] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 1, medium-density polyethylene resin 1, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 5 minutes, stirred evenly, melt-extruded and granulated by a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 160° C. for the first section, 170° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 220° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0059] Example 2

[0060] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0061] High density polyethylene resin 1: 63.7%

[0062] Medium density polyethylene resin 1: 10%

[0063] Linear low density polyethylene resin 1: 10%

[0064] Di-tert-butyl peroxide: 6%

[0065] Activated calcium carbonate: 5%

[0066] Lignocellulose: 5%

[0067] Antioxidant: 0.3%.

[0068] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0069] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 1 and the wood cellulose, and melt-extruding and granulating them using a low-shear wide-screw single-screw extruder, wherein the temperatures of each section of the single-screw extruder are 130° C. for the first section, 150° C. for the second section, 170° C. for the third section, 180° C. for the fourth section, and 190° C. for the fifth section, to obtain a mixture;

[0070] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 1, medium-density polyethylene resin 1, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 6 minutes, stirred evenly, melt-extruded and granulated by a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 160° C. for the first section, 180° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 220° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0071] Example 3

[0072] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0073] High density polyethylene resin 1: 39.9%

[0074] Medium density polyethylene resin 1: 20%

[0075] Linear low density polyethylene resin 1: 20%

[0076] Di-tert-butyl peroxide: 5%

[0077] Activated calcium carbonate: 10%

[0078] Lignocellulose: 5%

[0079] Antioxidant: 0.1%.

[0080] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0081] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 1 and the wood cellulose, and melt-extruding and granulating them using a low-shear wide-screw single-screw extruder, wherein the temperatures of each section of the single-screw extruder are 130° C. for the first section, 150° C. for the second section, 170° C. for the third section, 180° C. for the fourth section, and 180° C. for the fifth section, to obtain a mixture;

[0082] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 1, medium-density polyethylene resin 1, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 5 minutes, stirred evenly, melt-extruded and granulated by a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 150° C. for the first section, 170° C. for the second section, 190° C. for the third section, 210° C. for the fourth section, 220° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0083] Example 4

[0084] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0085] High density polyethylene resin 1: 47.8%

[0086] Medium density polyethylene resin 1: 10%

[0087] Linear low density polyethylene resin 1: 20%

[0088] Di-tert-butyl peroxide: 4%

[0089] Activated calcium carbonate: 8%

[0090] Lignocellulose: 10%

[0091] Antioxidant: 0.2%.

[0092] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0093] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 1 and the wood cellulose, and melt-extruding and granulating them using a low-shear wide-screw single-screw extruder, wherein the temperatures of each section of the single-screw extruder are 130° C. for the first section, 150° C. for the second section, 170° C. for the third section, 180° C. for the fourth section, and 190° C. for the fifth section, to obtain a mixture;

[0094] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 1, medium-density polyethylene resin 1, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 4 minutes, stirred evenly, melt-extruded and granulated by a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0095] Example 5

[0096] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0097] High density polyethylene resin 2: 50.8%

[0098] Medium density polyethylene resin 2: 10%

[0099] Linear low density polyethylene resin 2: 20%

[0100] Di-tert-butyl peroxide: 4%

[0101] Activated calcium carbonate: 10%

[0102] Glass Fiber: 5%

[0103] Antioxidant: 0.2%.

[0104] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0105] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 2 and the glass fiber, and melt-extruding and granulating them by a low-shear wide-thread single-screw extruder, wherein the temperature of each section of the single-screw extruder is 130° C. for the first section, 140° C. for the second section, 160° C. for the third section, 170° C. for the fourth section, and 180° C. for the fifth section, to obtain a mixture;

[0106] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 2, medium-density polyethylene resin 2, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 6 minutes, stirred evenly, melt-extruded and granulated in a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0107] Example 6

[0108] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0109] High density polyethylene resin 2: 51.8%

[0110] Medium density polyethylene resin 2: 20%

[0111] Linear low density polyethylene resin 2: 10%

[0112] Di-tert-butyl peroxide: 3%

[0113] Activated calcium carbonate: 8%

[0114] Glass Fiber: 7%

[0115] Antioxidant: 0.2%.

[0116] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0117] (1) Weighing the components of the composition in proportion, stirring and mixing the linear low-density polyethylene resin 2 and the glass fiber, and melt-extruding and granulating them by a low-shear wide-thread single-screw extruder, wherein the temperature of each section of the single-screw extruder is 140° C. for the first section, 150° C. for the second section, 170° C. for the third section, 180° C. for the fourth section, and 190° C. for the fifth section, to obtain a mixture;

[0118] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 2, medium-density polyethylene resin 2, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 5 minutes, stirred evenly, melt-extruded and granulated in a twin-screw extruder, and the temperature of each section of the twin-screw extruder is 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0119] Example 7

[0120] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0121] High density polyethylene resin 2: 39.7%

[0122] Medium density polyethylene resin 2: 20%

[0123] Linear low density polyethylene resin 2: 20%

[0124] Di-tert-butyl peroxide: 5%

[0125] Activated calcium carbonate: 7%

[0126] Glass Fiber: 8%

[0127] Antioxidant: 0.3%.

[0128] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0129] (1) Weighing the components of the composition in proportion, mixing the linear low-density polyethylene resin 2 and the glass fiber, and melt-extruding and granulating them by a low-shear wide-thread single-screw extruder, wherein the temperature of each section of the single-screw extruder is 130° C. for the first section, 140° C. for the second section, 160° C. for the third section, 170° C. for the fourth section, and 180° C. for the fifth section, to obtain a mixture;

[0130] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 2, medium-density polyethylene resin 2, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 5 minutes, stirred evenly, melt-extruded and granulated in a twin-screw extruder, and the temperature of each section of the twin-screw extruder is 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0131] Example 8

[0132] The high-strength polyethylene composition comprises the following raw materials in percentage by weight:

[0133] High density polyethylene resin 2: 58.9%

[0134] Medium density polyethylene resin 2: 10%

[0135] Linear low density polyethylene resin 2: 10%

[0136] Di-tert-butyl peroxide: 6%

[0137] Activated calcium carbonate: 5%

[0138] Glass Fiber: 10%

[0139] Antioxidant: 0.1%.

[0140] The preparation method of the high-strength polyethylene composition comprises the following steps:

[0141] (1) Weighing the components of the composition in proportion, stirring and mixing the linear low-density polyethylene resin 2 and the glass fiber, and melt-extruding and granulating them by a low-shear wide-thread single-screw extruder, wherein the temperature of each section of the single-screw extruder is 140° C. for the first section, 150° C. for the second section, 170° C. for the third section, 180° C. for the fourth section, and 190° C. for the fifth section, to obtain a mixture;

[0142] (2) The mixture obtained in step (1) is mixed with high-density polyethylene resin 2, medium-density polyethylene resin 2, di-tert-butyl peroxide, activated calcium carbonate and an antioxidant, mixed in a high-speed stirrer for 6 minutes, stirred evenly, melt-extruded and granulated in a twin-screw extruder, and the temperatures of each section of the twin-screw extruder are 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a high-strength polyethylene composition.

[0143] Comparative Example 1

[0144] The polyethylene composition comprises the following raw materials in percentage by weight:

[0145] High density polyethylene resin 1: 78.8%

[0146] Medium density polyethylene resin 1: 0%

[0147] Linear low density polyethylene resin 1: 0%

[0148] Di-tert-butyl peroxide: 3%

[0149] Activated calcium carbonate: 8%

[0150] Lignocellulose: 10%

[0151] Antioxidant: 0.2%.

[0152] The preparation method of the polyethylene composition is the same as that of Example 1.

[0153] Comparative Example 2

[0154] The polyethylene composition comprises the following raw materials in percentage by weight:

[0155] High density polyethylene resin 1: 54.7%

[0156] Medium density polyethylene resin 1: 10%

[0157] Linear low density polyethylene resin 1: 15%

[0158] Di-tert-butyl peroxide: 5%

[0159] Activated calcium carbonate: 15%

[0160] Lignocellulose: 0%

[0161] Antioxidant: 0.3%.

[0162] The preparation method of the polyethylene composition is the same as that of Example 1.

[0163] Comparative Example 3

[0164] The polyethylene composition comprises the following raw materials in percentage by weight:

[0165] High density polyethylene resin 1: 55.8%

[0166] Medium density polyethylene resin 1: 15%

[0167] Linear low density polyethylene resin 1: 15%

[0168] Di-tert-butyl peroxide: 4%

[0169] Activated calcium carbonate: 0%

[0170] Lignocellulose: 10%

[0171] Antioxidant: 0.2%.

[0172] The preparation method of the polyethylene composition is the same as that of Example 1.

[0173] Comparative Example 4

[0174] The polyethylene composition comprises the following raw materials in percentage by weight:

[0175] High density polyethylene resin 1: 58.8%

[0176] Medium density polyethylene resin 1: 20%

[0177] Linear low density polyethylene resin 1: 0%

[0178] Di-tert-butyl peroxide: 3%

[0179] Activated calcium carbonate: 8%

[0180] Lignocellulose: 10%

[0181] Antioxidant: 0.2%.

[0182] The preparation method of the polyethylene composition is the same as that of Example 1.

[0183] Comparative Example 5

[0184] The polyethylene composition comprises the following raw materials in percentage by weight:

[0185] High density polyethylene resin 3: 52.8%

[0186] Medium density polyethylene resin 1: 15%

[0187] Linear low density polyethylene resin 1: 15%

[0188] Di-tert-butyl peroxide: 3%

[0189] Activated calcium carbonate: 9%

[0190] Lignocellulose: 5%

[0191] Antioxidant: 0.2%.

[0192] The preparation method of the polyethylene composition is the same as that of Example 1.

[0193] Comparative Example 6

[0194] The polyethylene composition comprises the following raw materials in percentage by weight:

[0195] High density polyethylene resin 1: 63.7%

[0196] Medium density polyethylene resin 3: 10%

[0197] Linear low density polyethylene resin 1: 10%

[0198] Di-tert-butyl peroxide: 6%

[0199] Activated calcium carbonate: 5%

[0200] Lignocellulose: 5%

[0201] Antioxidant: 0.3%.

[0202] The preparation method of the polyethylene composition is the same as that of Example 1.

[0203] Comparative Example 7

[0204] The polyethylene composition comprises the following raw materials in percentage by weight:

[0205] High density polyethylene resin 2: 39.7%

[0206] Medium density polyethylene resin 2: 20%

[0207] Linear low density polyethylene resin 2: 20%

[0208] Di-tert-butyl peroxide: 5%

[0209] Activated calcium carbonate: 7%

[0210] Glass Fiber: 8%

[0211] Antioxidant: 0.3%.

[0212] The preparation method of the polyethylene composition comprises the following steps:

[0213] (1) Weigh each component in proportion, mix in a high-speed stirrer for 5 minutes, add to a twin-screw extruder for melt extrusion and granulation, the temperature of each section of the twin-screw extruder is 150° C. for the first section, 160° C. for the second section, 190° C. for the third section, 200° C. for the fourth section, 210° C. for the fifth section and 230° C. for the sixth section, to obtain a polyethylene composition.

[0214] Performance Testing:

[0215] During the test, relevant specimens were prepared by compression molding and stamping. The temperature of the upper and lower pressure plates was 220°C. They were preheated for 8 minutes and maintained at a pressure of 10 MPa for 5 minutes. Then cooling water was introduced to cool the specimen to room temperature. The pressure was maintained above 8 MPa during the cooling process. The test method is as follows.

[0216] Conditioning of the specimen and standard test environment: in accordance with the provisions of GB / T 2918-1998, the temperature is 23±2℃, the relative humidity is 50±5%, and the specimen conditioning time is based on the specific standards of the test items;

[0217] Density: Tested according to GB / T 1033.1-2008;

[0218] Simple supported beam notched impact strength: tested according to GB / T 1043.1-2008, the normal temperature treatment process is placed at 23℃ and 50% humidity for 24 hours;

[0219] Bending elastic modulus: according to GB / T 9341-2008;

[0220] High temperature creep test: stretch the specimen, select the middle part of the specimen and make a 50mm mark as the initial length, place the specimen at 23℃ and apply a tensile force of 120N, record the length change between the specimen marks after different time periods, and calculate the creep elongation with reference to the initial length.

[0221] Environmental stress cracking performance: According to GB / T 1842-2008, the test temperature is 50℃;

[0222] Shrinkage rate: mold a 20cm square piece with a thickness of 4mm, test the size of the sample after leaving it for 24 hours, and calculate the shrinkage rate based on the mold frame size.

[0223] Main test instruments: density meter; universal material testing machine, ZWICK; impact strength tester, CEAST, Italy; stress cracking tester, Jinjian; creep tester, ZWICK. Test results are shown in Table 1-5.

[0224] Table 1 Composition and performance of Examples 1-4

[0225]

[0226]

[0227] It can be seen from the test data in Table 1 that the high-strength polyethylene compositions prepared in Examples 1-4 have higher flexural elastic modulus and impact strength, as well as lower shrinkage, good environmental stress cracking resistance and creep resistance.

[0228] Table 2 Composition and performance of Examples 5-8

[0229]

[0230] It can be seen from the test data in Table 2 that the high-strength polyethylene compositions prepared in Examples 5-8 have higher flexural elastic modulus and impact strength, as well as lower shrinkage, good environmental stress cracking resistance and creep resistance.

[0231] Table 3 Comparative Examples 1-4 Formulation Composition and Performance

[0232]

[0233]

[0234] From the test data in Table 3, it can be seen that the stress cracking resistance time of Comparative Example 1 is significantly shortened and the shrinkage rate is also increased. The bending elastic modulus of Comparative Example 2 is significantly reduced, and the shrinkage rate and creep elongation index are not ideal. The shrinkage rate of Comparative Example 3 is increased compared with the embodiment. The test results of Comparative Example 4 show that the stress cracking resistance time is significantly shortened, the molding shrinkage rate and creep performance are not ideal, and the bending performance is also reduced.

[0235] Table 4 Comparative Examples 5-6 Formulation Composition and Performance

[0236]

[0237] It can be seen from Table 4 that the comprehensive properties of the compositions prepared in Comparative Examples 5-6 are reduced, especially in terms of creep elongation and molding shrinkage.

[0238] Table 5 Performance of Comparative Example 7

[0239]

[0240] It can be seen from Table 5 that the composition prepared in Comparative Example 7 has obvious declines in creep resistance, elongation and bending properties.

[0241] Products such as pallets and plates prepared from the high-strength polyethylene composition described in the present invention have the advantages of high strength, good impact resistance, low shrinkage, etc., and also have good stress cracking resistance, can be recycled multiple times, and the products can be used for a long time under conditions of stress bending, deformation, etc., and have been put into practical application in transportation.

Claims

1. A high-strength polyethylene composition, characterized in that The following raw materials are included in weight percentage: High-density polyethylene resin: 33.7-68.9% Medium density polyethylene resin: 10-20% Linear low density polyethylene resin: 10-20% Peroxide crosslinker: 1-6% Activated calcium carbonate: 5-10% Reinforcement fiber: 5-10% Antioxidant: 0.1-0.3%.

2. The high-strength polyethylene composition according to claim 1, characterized in that: The high-density polyethylene resin has 1-hexene as a comonomer, and the content of the comonomer is 0.8-1.0%; the melt mass flow rate of the high-density polyethylene resin is 0.2-1g / 10min at a temperature of 190°C and a weight of 5kg; the density is 0.948-0.953g / cm 3 ; Weight average molecular weight is (20-35)×10 4 ; The molecular weight distribution width is 25-35.

3. The high-strength polyethylene composition according to claim 1, characterized in that The medium density polyethylene resin uses 1-hexene as a comonomer, and the content of the comonomer is 1-1.2%; the melt mass flow rate of the medium density polyethylene resin is 0.3-1g / 10min at a temperature of 190°C and a weight of 2.16kg; the melt mass flow rate is 15-25g / 10min at a temperature of 190°C and a weight of 21.6kg, the melt flow ratio is 30-60, and the density is 0.935-0.940g / cm 3 , the number of long chain branches with a length greater than 6 carbon atoms in the molecule is more than 5 / 1000C.

4. The high-strength polyethylene composition according to claim 1, characterized in that: The melt mass flow rate of the linear low-density polyethylene resin is 1.5-2.5 g / 10 min at a temperature of 190°C and a weight of 2.16 kg, and the density is 0.917-0.923 g / cm 3 .

5. The high-strength polyethylene composition according to claim 1, characterized in that: The peroxide crosslinking agent is one or more of alkyl peroxide, aryl peroxide, acyl peroxide or ketone peroxide.

6. The high-strength polyethylene composition according to claim 1, characterized in that: The activation degree of the activated calcium carbonate is above 98%. The preparation method is as follows: putting the dried calcium carbonate into a mixer and heating it to above 80°C, adding an activator, and obtaining the activated calcium carbonate; the particle size of the calcium carbonate is 800-2000 meshes.

7. The high-strength polyethylene composition according to claim 1, characterized in that: The aspect ratio of the reinforcing fiber is greater than 100:1, and the reinforcing fiber is one of carbon fiber, glass fiber or wood cellulose.

8. The high-strength polyethylene composition according to claim 1, characterized in that: The antioxidant is obtained by mixing antioxidant 1010 and antioxidant 168, and the mixing ratio is 1:(0.5-2).

9. A method for preparing the high-strength polyethylene composition according to any one of claims 1 to 8, characterized in that: Here are the steps: (1) mixing a linear low-density polyethylene resin and reinforcing fibers, and melt-extruding and granulating the mixture using a single-screw extruder; (2) The mixture obtained in step (1) is mixed with a high-density polyethylene resin, a medium-density polyethylene resin, a peroxide crosslinking agent, activated calcium carbonate and an antioxidant, stirred evenly, melt-extruded and granulated through a twin-screw extruder, and a high-strength polyethylene composition is obtained.

10. The method for preparing a high-strength polyethylene composition according to claim 9, characterized in that: In the step (1), the extrusion temperature of the single screw is 130-190°C; and in the step (2), the extrusion temperature of the twin screw is 150-230°C.

Citation Information

Patent Citations

  • Bamboo-plastic composite board material for container bottom board

    CN113930039A